POTENSI DAN KENDALA PENGEMBANGAN WISATA SYARIAH PADA OBJEK WISATA PULAU KUMAYAN - Utami, Dwi Subekti Puji; Isnaini, Desi; Hanif, Padlim (ITB AAS Indonesia Surakarta, 2024)
This research aims to find out the potential for sharia tourism development on the Kumayan Island tourist attraction and what are the obstacles to development on the Kumayan Island tourist attraction. This research uses qualitative methods based on the philosophy of postpositivism. With data collection techniques in the form of observation, interviews and documentation. The primary data in this research are managers and visitors at the Kumayan Island tourist attraction. The research results state that Kumayan Island has great potential to be developed as a sharia tourism destination, considering its unspoiled natural beauty and local wisdom of the local community. The development of the Kumayan Island tourist attraction faces several main obstacles, such as limited infrastructure, inadequate accessibility, and limited human resources trained in the tourism industry.